A systematic review on the usability of web-based applications in advocating consumers on food safety - Seow, Wen-Li; Md Ariffin, Umi Kalsom; Lim, Sook Yee; Mohamed, Nurul Azmawati; Lee, Kai Wei; Devaraj, Navin Kumar; Amin-Nordin, Syafinaz (MDPI, 2022)
Food safety is an important indicator of public health, as foodborne illnesses continue to cause productivity and economic loss. In recent years, web-based applications have been extensively used by the online users’ population. Almost one third (28.3%) of online users found web-based application to be a notable source of food safety information. The objective of the current review is to determine the effectiveness of a web-based application systems as a health promotion tool for consumers to increase their knowledge and awareness of food safety. A systematic literature review was conducted by analyzing 11 selected web-based food safety education-related articles. The studies were categorized into several themes: (1) web-based applications used in accessing food safety information; (2) food safety evaluation and perception among consumers; (3) beliefs and level of knowledge, attitude and practices (KAP) of consumers; and (4) impact and contribution of social media use. A diverse number of online applications have been utilized to promote food safety education among consumers, yet these web-based applications need to be improved with regards to social connection and integration among consumers. KAP surveys were conducted on the majority of the respondents with a particular focus on their knowledge level. Findings show that web-based applications may act as an alternative to the traditional media in enhancing food safety education among consumers, especially youths who are tech-savvy.